Disparities in patient-centered communication for Black and Latino men in the U.S.: Cross-sectional results from the 2010 health and retirement study - Jamie A. Mitchell; Ramona Perry; Baltica Cabieses (PLoS ONE, 2020)
Background A lack of patient-centered communication (PCC) with health providers plays an important role in perpetuating disparities in health care outcomes and experiences for minority men. This study aimed to identify factors associated with any racial differences in the experience of PCC among Black and Latino men in a nationally representative sample. Methods We employed a cross-sectional analysis of four indicators of PCC representative of interactions with doctors and nurses from (N = 3082) non-Latino White, Latino, and Black males from the 2010 Health and Retirement Study (HRS) Core and the linked HRS Health Care Mail in Survey (HCMS). Men’s mean age was 66.76 years. The primary independent variable was Race/Ethnicity (i.e. Black and Hispanic/Latino compared to white males) and covariates included age, education, marital status, insurance status, place of care, and self-rated health. Results Bivariate manova analyses revealed racial differences across each of the four facets of PCC experience such that non-Hispanic white men reported PC experiences most frequently followed by black then Hispanic/Latino men. Multivariate linear regressions predictive of PCC by race/ethnicity revealed that for Black men, fewer PCC experiences were predicted by discriminatory experiences, reporting fewer chronic conditions and a lack of insurance coverage. For Hispanic/Latino men, access to a provider proved key where not having a place of usual care solely predicted lower PCC frequency. Implications Researchers and health practitioners should continue to explore the impact of inadequate health care coverage, time-limited medical visits and implicit racial bias on medical encounters for underrepresented patients, and to advocate for accessible, inclusive and responsive communication between minority male patients and their health providers.